CEFR for Languages and Its Effective Implementation in Secondary Schools in Malaysia - Md Nawawi, Norshaidatul; Zuhaimi, Natasha; Sabu, Khairunisa; Mahamud, Nur Siti Rozaialaina; Moh Nasir, Nur Afiqah (Asian Journal of Assessment in Teaching and Learning, 2021)
The implementation and development of the Common European Framework of References (CEFR) have received recognition and enthusiasm in language learning globally. The purpose of the present study, therefore, is to investigate the effectiveness of the implementation of CEFR reference of language in other countries generally as well as in the Malaysian secondary schools specifically. The evaluation of Malaysian teachers’ perceptions toward the implementation of CEFR is substantially important to carry out the significant problems of implementing the framework. A systematic literature review was done to several research studies in Asian and especially Malaysia to achieve the fundamental research objectives. Despite the several challenges faced by English Second Language (ESL) teachers in implementing the framework. Therefore, it was found that CEFR has potentially improved in the language learning context.